Mechanism of Gas Conductivity of GCLs - Tondkar, Matin; Chegenizadeh, Amin; Nikraz, Hamid (Planetary Scientific Research Centre, 2012)
Diffusion of gas from waste landfills can be harmful for human health. Due to this reason a combination layers of geosynthetic clay liner–geomembrane (GCL/GM) is used as a barrier in waste landfills nowadays. Knowledge of gas diffusion from GCL/GM is vital in order to prevent its diffusion. This paper discussed laboratory works performed on gas transfer through the soil matrix from GCL/GM layers. This paper summarized the main previous investigation on this area and finally will conclude the main outcomes of these researches.